2017
DOI: 10.1007/s00405-017-4641-5
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient versus observation/inpatient parotidectomy: patient factors and perioperative complications

Abstract: The objective of this manuscript is to review a single institution's experience with superficial or total parotidectomy in outpatient and observation/inpatient groups. All patients who underwent superficial or total parotidectomy between 2009 and 2015 were identified. Patients were excluded if they had undergone concurrent surgery such as neck dissection, had prior radiation treatment or surgery at the operative site. Main outcomes were perioperative complications in both groups. 215 consecutive patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 6 publications
2
58
0
1
Order By: Relevance
“…One single-institutional analysis comparing superficial and total parotidectomies performed as an outpatient versus inpatient procedure found comparatively low rates of procedure-specific complications in the outpatient cohort, concluding that these procedures can be performed safely without overnight observation. 15 Another study at the Fallon Clinic (Worcester, MA) similarly reported low complication rates and modest savings from same-day parotidectomies. 11 The studies on outpatient thyroidectomies are more extensive and report similar results in which the outpatient cohort have significantly reduced rates of complications.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…One single-institutional analysis comparing superficial and total parotidectomies performed as an outpatient versus inpatient procedure found comparatively low rates of procedure-specific complications in the outpatient cohort, concluding that these procedures can be performed safely without overnight observation. 15 Another study at the Fallon Clinic (Worcester, MA) similarly reported low complication rates and modest savings from same-day parotidectomies. 11 The studies on outpatient thyroidectomies are more extensive and report similar results in which the outpatient cohort have significantly reduced rates of complications.…”
Section: Discussionmentioning
confidence: 98%
“…This analysis indicates no differences in patient readmissions following inpatient or outpatient parotidectomy, along with lower rates of reoperation succeeding outpatient parotidectomies prior to matched analysis (Table V). Low rates of readmission and reoperation after ambulatory parotidectomies have been demonstrated in smaller studies, 15,17 although patients with more comorbidities are more likely to be inpatient and thus may be more likely to require a reoperation. The literature emphasizes the importance of patient competency for postoperative care and frequent follow-up after outpatient surgery, 4 which may be paramount to preventing readmissions and reoperations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics along with patient demographics are summarized in Table 1. Eleven studies were retrospective cohort studies 7,25‐32,34,35 . Two prospective cohort studies were included 16,33 .…”
Section: Resultsmentioning
confidence: 99%